Exploring services science : 8th International Conference, IESS 2017, Rome, Italy, May 24-26, 2017, Proceedings /: 8th International Conference, IESS 2017, Rome, Italy, May 24-26, 2017, Proceedings. (2017) - Unknown
No abstract available